PHYTO-SYNTHESIS OF CdO NPs BY CRUDE EXTRACT OF POLYGONUM MULTIFORUM - Abdulhadi , B .H.; Abdul Jalill, R. DH.; Abd, A. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The goal of this research is to detect flavonoids in Polygonum multiforum and use these extracts in the phyto-synthesis of (CdO NPs) Nano-particles (CdO, CdO2) and characterize them.  The HPLC examination yielded five compounds: Emodin (29.55%), followed by Aloe-emodin (24.52%), Chrysophanol (19.24%), Rhein (16.61%), and Physcion (10.06%). Two techniques were utilized to synthesize NPs, and the average size (by AFM) was (83.26 and 86.14) nm for the first and second procedures, respectively. SEM analysis revealed that process 1 produced Nano-rod particles with diameters ranging from (20-50) nm, whereas procedure 2 produced hexagonal Nano-plate crystals with a single Nano-scale size (20-100) nm. TEM pictures showed the same characteristics.  For processes 1 and 2, the FTIR analysis showed prominent bands at 524 and 532.4 (1/cm), respectively. This was ascribed to stretching vibrations in Cd-O.